Body bugs : uninvited guests on your body - Day, Trevor (Mankato, Minn. : Capstone Press, 2008)
Describes microorganisms and insects that live on and in the human body.
Nice home! -- Feeling lousy? -- Open wide -- Mucus anyone? -- Sniffing you out! -- Fighting invasion! -- Ticked off -- A flea in your ear -- It's in the blood -- Boring worms -- Getting to the guts -- What a waste! -- Stinky feet.
Includes bibliographical references (p. 31) and index.
Horn Book.
Horn Book, October 2009.
5.5
3-6
Keywords: Microorganisms -- Juvenile literature; Microorganisms; Microorganisms